Indigenous ecotourism in the Mayan rainforest of Palenque: empowerment issues in sustainable development - Ramos, Adrian Mendoza; Prideaux, Bruce (Journal of sustainable tourism, 2014)
Indigenous ecotourism in the Mayan rainforest has received little research attention. This study examines issues related to the level of empowerment in a Mayan village located near the Palenque World Heritage Site in southern Mexico. An adapted empowerment framework was used to assess community empowerment and its relationship with stakeholders' participation by collecting the views of internal and external stakeholders in indigenous ecotourism. Using a checklist of 60 empowerment indicators, the study developed a wheel of empowerment tool that graphically illustrates and compares levels of empowerment/disempowerment in local communities. Results indicate that although there is a will from many villagers to participate in tourism, lack of knowledge, limited economic resources and the poor negotiation skills of local leaders have disempowered the community from undertaking ecotourism ventures. Non Governmental Organisations (NGOs) have not supported the community until recently, the private sector has played little part, and while the Mexican government is shaping the course of indigenous ecotourism with support programmes, state agencies have resisted local ecotourism development. Overall, the community fell below the midpoint on the Wheel of Empowerment Scale. These findings show a need for more effective empowerment strategies to maximise community involvement in managing cultural and natural resources for tourism development.